Experimental Modeling of Natural Processes of Nepheline Alteration - Julia A. Mikhailova; Galina O. Kalashnikova; Yakov A. Pakhomovsky; Ekaterina A. Selivanova; Alena A. Kompanchenko (Minerals, 2023)
Nepheline, ideally Na3K(Al4Si4O16) is a key mineral of silica-undersaturated igneous rocks. Under subsolidus conditions, nepheline is intensively replaced by numerous secondary minerals, of which various zeolites (mainly natrolite, analcime, gonnardite), as well as cancrinite, muscovite and Al-O-H phases (gibbsite, böhmite, nordstrandite) are the most common. In the rocks of the Lovozero alkaline massif (Kola Peninsula, NW Russia), nepheline is extensively replaced by the association natrolite + nordstrandite ± böhmite ± paranatrolite. To reproduce the conditions for the formation of such a mineral association, a series of experiments were carried out on the dissolution of nepheline in deionized water, 0.5 mol/L NaCl, 0.5 mol/L NaOH, and 0.1 mol/L HCl at 230 °C for 1/5/15 days. When nepheline is partially dissolved, phases and mixtures of phases precipitate on the surface of its grains, and these phases were diagnosed using X-ray powder diffraction and Raman spectroscopy. Observations in natural samples and experimental studies have shown that the nepheline alteration in the rocks of the Lovozero massif with the formation of natrolite and Al-O-H phases occurred under the influence of a high to medium salinity solution at a pH of near 6.